1982
DOI: 10.1001/archotol.1982.00790490017004
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the Performance-Intensity Functions for Phonetically Balanced Word Lists and Synthetic Sentences in Aged Listeners

Abstract: \s=b\The performance intensity-phonetically balanced (PI-PB) and performance intensity-synthetic sentence identification (PI-SSI) functions were determined for 62 elderly patients (100 ears) with presbyacusis. A comparison of these functions was performed to determine whether patients older than 60 years exhibited peripheral or central PI-PB/PI-SSI patterning. Fifty-eight ears of the 100 ears examined showed central patterning. Furthermore, two diagnostically important central patterns were identified. The imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1
3

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
4
13
1
3
Order By: Relevance
“…The results obtained in this investigation are in general agreement with the results obtained by others in previous investigations [Hayes and Jerger, 1979;Jerger and Hayes, 1977;Shirinian and Arnst, 1982]; a signifi cant number of the geriatric clients (6 of 19 in this investigation) showed evidence of a central aging effect with the right ear being slightly more likely to be affected than the left ear.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained in this investigation are in general agreement with the results obtained by others in previous investigations [Hayes and Jerger, 1979;Jerger and Hayes, 1977;Shirinian and Arnst, 1982]; a signifi cant number of the geriatric clients (6 of 19 in this investigation) showed evidence of a central aging effect with the right ear being slightly more likely to be affected than the left ear.…”
Section: Discussionsupporting
confidence: 92%
“…They also noted that the effect tended to be somewhat greater for the right ear. Shirinian and Arnst [ 1982] also noted sig nificant central effects in many of their el derly (age 60-85) listeners. Of the 100 ears in their sample, more than half [58] showed sig nificant central aging effects.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Vários estudos da literatura especializada aplicaram o SSI em idosos e verificaram resultados semelhantes em relação ao desempenho das orelhas direita e esquerda 14,[20][21][22][23] . No presente estudo, verificamos desempenho bom no teste PSI à orelha direita (Tabelas 4 e 5) na condição PSI (0) e PSI (-10), respectivamente em 91 indivíduos (82,7%) e em 78 indivíduos (70,9%).…”
Section: Discussionunclassified
“…Interestingly, such an effect has, indeed, been noted. Investigators have demonstrated greater decline in the left ear with increasing age for time-compressed monosyllabic words (Konkle, Beasley, & Bess, 1977) and for SSI sentences (Shirinian & Arnst, 1982).…”
Section: Discussionmentioning
confidence: 99%